Side Effects and Solutions of CAR-T Treatment - Yao, Zhijie (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Cancer poses a significant threat to human health. It is a kind of complex and severe diseases characterized by the expanding of abnormal cells in the whole body due to uncontrolled growth. If left untreated, cancer with metastasis can invade nearby tissues, spread to other parts of the body, and impair the normal functioning of organs and systems. There are some treatment methods for it, such as surgery, chemical therapy and radiation. The field of immunology has made tremendous strides in understanding how the immune system works and how it can be harnessed to fight disease. Immunotherapy has become a rising solution in recent years. CAR-T therapy belongs to immunotherapy using genetically modified T cells with receptors of tumor antigens to specifically eliminate cancer cells, which is a promising approach for cancer patients. However, there are still some issues that remain to be resolved to make it wider using in treatment of cancer patients. For example, CAR-T therapy occurs severe side effects sometimes, even induced patients die, although it has been approved application in clinic since 2017, however, limited studies investigated its adverse reactions. Therefore, in the present, the author provides a comprehensive overview of the side effects of CAR-T therapy from reduction of therapeutic effects of antigen escape, to induction patients die of severe cytokine storms, then discusses corresponding treatment measures, which purpose is to help guide treatment for patients, make clinical staff focus on its side effects and provide some ideas for research and development in the future.